2022
DOI: 10.3390/ijerph19041956
|View full text |Cite
|
Sign up to set email alerts
|

Social Health among German Nursing Home Residents with Dementia during the COVID-19 Pandemic, and the Role of Technology to Promote Social Participation

Abstract: The COVID-19 pandemic severely impacted the social health of nursing home residents with dementia due to social isolation. Consequently, the frequency of Behavioral and Psychological Symptoms in Dementia (BPSD) might increase. Technological solutions might help safeguard the social health of nursing home residents with dementia. This study investigates the impacts of the COVID-19 pandemic on clinical outcomes and the availability of social activities and technology to promote social participation in nursing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…During the pandemic, studies have reported difficulties in supplying people living with dementia sufficient medical care. People living with dementia at care homes have experienced varying levels of social isolation and decrease in mental stimuli [ 45 , 46 ]. Also home dwelling elderly with dementia and their care givers have reported loss of daily habits, loneliness and struggles to access regular health care [ 47 – 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, studies have reported difficulties in supplying people living with dementia sufficient medical care. People living with dementia at care homes have experienced varying levels of social isolation and decrease in mental stimuli [ 45 , 46 ]. Also home dwelling elderly with dementia and their care givers have reported loss of daily habits, loneliness and struggles to access regular health care [ 47 – 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment in interventions targeting formal caregiving relationships seems to require space dedicated to enabling social interactions beyond custodial care. Considerations such as protected time and explicit training on socially oriented care may be necessary (109)(110)(111) to allow positive relationships to emerge and grow. Interventions targeting informal dyads, on the other hand, may consider building on the dyads' shared history and sustain or enhance their caregiving relationship by including components that may circumvent the challenges that follow when living with dementia, such as emotional support, coping and management strategy training or dementia-friendly shared activities.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…An increasing area of interest in psychosocial interventions in dementia is digital technologies [ 26 , 27 ]. However, progress in technological interventions supporting relationships through interaction and communication for this population is still in its infancy [ 9 , 28 , 29 ]. For this study, we utilise the term ’social technology’, defined as “any technology that facilitates social interactions and influences social processes between people” [ 30 ] (p. 3).…”
Section: Introductionmentioning
confidence: 99%